Popularity of body modifications and knowledge about their complications among young adults - Pekar, Joanna; Skolarczyk, Justyna Magdalena; Łabądź, Dawid Dominik; Chrobok, Katarzyna Honorata; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2017)
Background and objectives. Body modifications are practices leading to transient or permanent change of various parts of human body. The most popular forms of body modifications are: tattooing and piercing. The aim of the study is to determine the frequency of the most popular body modifications (tattoos and piercing) among young adults aged 18-32 years and to collect and analyze the opinion about body modifications and to determine their knowledge about the complications possible after these procedures. Material and methods. The study was conducted in February 2017 among 251 individuals: 146 females (58.17%) and 105 males (41.83%). An original questionnaire was used. It consisted of questions about body modifications. Researchers recorded body modifications the respondents have had. Participation in the study was voluntary and anonymous. Participants were randomly selected. Results were analyzed with STATISTICA 12.5 and ANOVA program; p<0.05 was considered statistically significant. Results. 23 examined individuals (10 men and 13 women) had tattoos (9.16%). The mean number of tattoos was 1.6 ±0.6 in women and 2±1.1 in men. 128 individuals had ear piercing (51%), including 6 males and 122 females. 13 people (5.18%) had piercing in places other than ears. Piercing is significantly more common than tattooing. 109 individuals (43.43%) did not have tattoos or body piercing. 106 respondents (42.23%) liked tattoos, ear piercing 168 (66.93%), piercing of other parts of the body 41 (16.33%), and other body modifications 8 (3.19%). 221 (88.05%) individuals claimed that they knew the complications of body modifications. Conclusion. Body modifications are popular among young adults, especially among females. The most positively the respondents assessed earrings and tattoos, which correlates with their occurrence in this group of people. Vast majority of respondents declared that they knew possible complications of body modifications.